RANKL-Expressing Ectopic Extramammary Paget's Disease on the Lower Abdomen - Akiko Hagiwara-Takita; Taku Fujimura; Aya Kakizaki; Setsuya Aiba (Karger Publishers, 2016)
Ectopic extramammary Paget's disease (EMPD) is a rare variant of EMPD that develops in nonapocrine regions. Since reports about ectopic EMPD are limited, little is known about the biological and immunological background of ectopic EMPD. In this report, we present a case of ectopic EMPD on the lower abdomen that expressed RANKL but lacked the expression of MMP7. As we previously reported, Paget's cells express RANKL and MMP7, release soluble RANKL in the tumor microenvironment, and stimulate tumor-associated macrophages to produce tumor-loading factors in conventional EMPD. In our present case, both CCL5-expressing cells and MMP25-bearing cells were lacking, whereas substantial numbers of CCL5-expressing cells and MMP25-bearing cells were found in conventional EMPD. Our case suggested that the lack of MMP7 on Paget's cells might be one of the possible explanations for the biology of ectopic EMPD.